Het uitgaan van de Sphinx-fabriek. Kopie van foto uit collectie van de Gemeentelijke Archiefdienst Maastricht
Het uitgaan van de Sphinx-fabriek. Kopie van foto uit collectie van de Gemeentelijke Archiefdienst Maastricht.